MENINGKATKAN KEMAMPUAN MEREPRESENTASIKAN MASALAH MELALUI PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Klarita One; Sofia Sa'o; Yasinta Yenita Dhiki (Program Studi Pendidikan Matematika, 2022)
This study aims (1) to find out student activities by applying realistic mathematics learning, SPLTV material in class X students of SMA Negeri 1 Ende for the 2021/2022 academic year, (2) to find out students' mathematical representation abilities by applying realistic mathematics learning, SPLTV material on class X SMA Negeri 1 Ende for the 2021/2022 Academic Year. The type of research used is Classroom Action Research (PTK) with data collection techniques namely observation, testing and documentation. This research occurred in two cycles with the same implementation stages. Based on the research data it can be concluded that learning planning using realistic mathematics learning received a positive response from students. This can be seen from the percentage of student activity of 69% in the pretty good category. Cycle II showed a very good change in activity, where the percentage of student activity was recorded at 94% in the very good category. The realistic mathematics learning used in this study also had a positive impact on students' mathematical representation abilities. Verbal representation ability 69.83% in cycle I increased to 79.3% in cycle II. The symbol representation ability of 68.22% in the first cycle increased to 85.33% in the second cycle. Therefore the researchers concluded that realistic mathematics learning can improve student learning activities and mathematical representation abilities of class X Sma Negeri 1 Ende.